Teachers' Strategies in Enhancing experience and Creating Fun Art Learning For Children Aged 3-6 years in PAUD Jabal Rahmah Yogyakarta - Aeni, Khapipatul; Pamungkas, Joko (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The To optimize children's art development in art learning activities, teachers must have the right strategy. Therefore, it is not only the right techniques and resources that are needed to enhance children's art development. The teacher's method of preparing for learning, as well as methods, media, and other elements, greatly affect the child's learning process. The purpose of this study is to provide an explanation of the methods teachers use to make art learning fun for students in kindergarten. The research was conducted in one month, during April 2024. The location of this research was conducted in one of the PAUD in Yogyakarta, namely Jabal rahmah PAUD. This qualitative descriptive study was designed as a case study. Data collection involved observation, documentation, and interviews. Presenting data, reducing data, and drawing conclusions were part of the data analysis conducted using the Miles Huberman model. The discussion of art learning strategies in early childhood at Jabal Rahmah PAUD shows that these strategies are quite different: direct and collaborative learning strategies with group and centre models proved to be fun and improved children's art skills. based on this, children are used to working together and are confident in their respective fields. in addition, teachers use art learning as part of teaching and learning activities, while extracurricular teachers conduct art form activities such as music, fine arts and dance. This is due to the difference between classroom teachers and teachers who teach outside the classroom, who have greater professional experience gained through arts education.